Quaternized modified PACE-Cl nanofiber as well as preparation method and application thereof
Quaternary amination modified PPACE-Cl nanofibers were prepared through electrospinning technology and surface grafting technology, which solved the problems of toxicity, complex operation and low efficiency of existing gold recovery technologies, and achieved high selective adsorption and efficient recovery of AuCl4-.
Patent Information
- Application Number
- CN202411817023.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The existing gold recycling technology has the toxicity and corrosiveness of cyanide and aqua regia, which is complex in operation, large waste liquid volume, low recovery rate, and low adsorbent efficiency and poor selectivity.
Nanofibers with polyacrylonitrile (PAN), polyvinylpyrrolidone (PVP) and carboxylated multi-walled carbon nanotubes (MWCNT-COOH) as matrix were prepared by electrospinning technology, and quaternary amination modified PPACE-Cl nanofibers were prepared by polyethyleneimine enriched nitriding and chloro-n-propane quaternary amination modification, and quaternary amination modified PPACE-Cl nanofibers were prepared as adsorption materials for selective recovery of AuCl4-.
High selective adsorption of AuCl4- is achieved, with a maximum adsorption capacity of 808.58 mg/g. The adsorption process complies with the quasi-secondary kinetic model and Langmuir isothermal adsorption model. It also exhibits high selectivity in complex, strongly acidic industrial wastewater environments, with a distribution coefficient of up to 9482.889 L/g.
Smart Images

Figure CN119531126A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanofibers, and in particular to a quaternary ammonium modified PPACE-Cl nanofiber and a preparation method and application thereof. Background Art
[0002] As a precious precious metal, gold is characterized by scarcity, durability, easy processing and non-corrosiveness, so it is given a high value. The main sources of gold are mining and recycling. The recycling of gold is of great significance. The mining and refining of gold consumes a lot of resources and energy. Recycling gold can reduce the loss of natural resources. The mining and refining of gold will pollute the environment, while the recycling of gold can reduce the damage to the environment and reduce the harm of waste to the environment. Recycling gold can reduce production costs and improve resource utilization efficiency. The recycling of gold is in line with the concept of circular economy and helps to build a resource-saving and environmentally friendly society. Therefore, the recycling of gold is of great significance for resource protection, environmental protection and sustainable development.
[0003] At present, the process of gold extraction generally consumes a large amount of cyanide, aqua regia and other compounds, but due to the toxicity of cyanide and the corrosiveness of aqua regia, it will cause serious harm to the environment and human health during use. In recent years, researchers have carried out a lot of research on environmentally friendly gold extraction technologies, such as leaching processes such as chlorination, thiosulfate, and thiourea, as well as purification processes such as solvent extraction and ion exchange. Traditional hydrometallurgy has the advantages of low energy consumption and easy control, but its recovery process is complicated to operate, with a large amount of waste liquid and a low recovery rate. At the same time, traditional gold recovery technology also has problems with low adsorbent efficiency and poor selectivity. Summary of the invention
[0004] Features and advantages of the invention are set forth in part in the following description, or may be obvious from the description, or may be learned through practice of the invention.
[0005] In order to overcome the problems of the prior art, the present invention provides a method for preparing quaternary ammonium modified PPACE-Cl nanofibers, which specifically comprises the following steps: S1. Preparation of PAN electrospinning nanofibers: polyacrylonitrile, polyvinyl pyrrolidone, and carboxylated multi-walled carbon nanotubes were stirred with N,N-dimethylformamide at room temperature for 6-12 hours to obtain a uniform and transparent spinning solution, and then the obtained spinning solution was placed in a 10 mL syringe and spun in an electrospinning machine to obtain PAN / PVP / MWCNT-COOH nanofibers, and then the obtained nanofibers were placed in 60-100°C hot water to remove PVP to obtain PAN / MWCNT-COOH nanofibers; S2. Preparation of nitrogen-enriched modified PPACE nanofibers: placing the PAN / MWCNT-COOH nanofibers prepared in step S1 and an aqueous solution of polyethyleneimine in a high-pressure reactor, reacting at 110-140°C for 12-24h, washing the nanofibers after the reaction with pure water for more than 3 times, and performing vacuum freeze drying at -50°C for 12h to obtain modified PPACE nanofibers; S3. Preparation of quaternized PPACE-Cl nanofibers: After mixing the PPACE nanofibers prepared in step S2 with n-propyl chloride, ethanol was added as a solvent, and refluxed for 8 to 12 hours under magnetic stirring at 80°C. After the reaction, the nanofibers were washed with ethanol three times, and vacuum freeze-dried at -50°C for 12 hours to obtain quaternized modified PPACE-Cl nanofibers.
[0006] Preferably, the mass ratio of the polyacrylonitrile, polyvinyl pyrrolidone, carboxylated multi-walled carbon nanotubes, and N,N-dimethylformamide is 1:1:1:9-16.
[0007] Preferably, the mass ratio of the PAN / MWCNT-COOH nanofibers to the polyethyleneimine aqueous solution is 1:10.
[0008] Preferably, the mass ratio of the PPACE nanofibers to the n-propyl chloride is 1:0.925-2.775.
[0009] Preferably, the parameters of the electrospinning machine are set as follows: voltage is 15.0-18.0 KV, spinning solution flow rate is 2.0 mL / h, drum speed is 200 r / min, receiving distance is 15 cm, spinning temperature and humidity are 25 ± 1 °C and 70 ± 5%, respectively.
[0010] The present invention also provides a quaternary ammonium modified PPACE-Cl nanofiber, wherein the quaternary ammonium modified PPACE-Cl nanofiber is prepared by the preparation method of the quaternary ammonium modified PPACE-Cl nanofiber as described above.
[0011] The present invention also provides an application of quaternary ammonium modified PPACE-Cl nanofibers, wherein the quaternary ammonium modified PPACE-Cl nanofibers are used as adsorption materials for AuCl4 - Selective recovery.
[0012] Beneficial effects of the present invention:
[0013] The present invention uses polyacrylonitrile (PAN), polyvinyl pyrrolidone (PVP) and carboxylated multi-walled carbon nanotubes (MWCNT-COOH) as matrix materials, prepares nanofibers by electrospinning technology, removes PVP to obtain porous PAN / MWCNT-COOH nanofibers, uses polyethyleneimine (PEI) as a nitrogen-enriched functional group, and then uses chlorinated n-propane for quaternary ammonium modification to prepare quaternary ammonium modified PPACE-Cl nanofibers. The nanofibers have good performance on AuCl4 - The maximum adsorption capacity of AuCl4 can reach 808.58 mg / g, and the adsorption process conforms to the pseudo-second-order kinetic model and the Langmuir isotherm adsorption model. - The high selectivity of AuCl4 - It has high selective adsorption capacity.
[0014] The quaternary ammonium modified PPACE-Cl nanofiber adsorption material prepared by combining electrospinning technology and surface grafting technology exhibits super hydrophilicity. The quaternary ammonium modified PPACE-Cl nanofiber prepared by the present invention has excellent hydrophilicity, reduces the energy barrier in the adsorption process, can significantly improve the adsorption rate and adsorption capacity, and provides a new technical method for the recovery of gold in wastewater.
[0015] The quaternized PPACE-Cl nanofibers prepared by the present invention have abundant nitrogen-containing groups, which can serve as adsorption sites for AuCl4 - There is a strong interaction between them, which leads to AuCl4 - In addition, since the quaternized PPACE-Cl nanofibers have good hydrophilicity, the contact energy barrier between them and gold in the solution can be reduced, and AuCl4 - Reduced to Au (0), thereby promoting the entire adsorption process.
[0016] The quaternized PPACE-Cl nanofibers of the present invention adopt a quaternized modification method to make the surface of the prepared nanofibers positively charged, so as to achieve the effect of reacting the AuCl4 in the aqueous solution with a negative charge. - Carry out selective enrichment adsorption.
[0017] The quaternized PPACE-Cl nanofibers of the present invention are - The adsorption process involves multiple reaction mechanisms such as electrostatic effect, coordination effect and redox reaction, so it has a higher adsorption capacity and better adsorption effect.
[0018] The quaternized PPACE-Cl nanofiber of the present invention exhibits superhydrophilicity, can reduce the contact energy barrier between the nanofiber and gold in the solution, can effectively solve the problem of gold adsorption, recovery and removal in a solution with a relatively high concentration, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The present invention will be described in detail below with reference to the accompanying drawings and in combination with examples, and the advantages and implementation methods of the present invention will become more obvious. The contents shown in the accompanying drawings are only used to explain the present invention and do not constitute any limitation to the present invention in any sense. In the accompanying drawings: Figure 1 The figure is a schematic flow chart of a method for preparing quaternary ammonium modified PPACE-Cl nanofibers in a specific embodiment of the present invention; Figure 2 The schematic diagram of the preparation process of a method for preparing quaternary ammonium modified PPACE-Cl nanofibers in a specific embodiment of the present invention; Figure 3 The scanning electron microscope images of the nanofibers at various stages obtained in the specific embodiment 3 of the present invention are shown in FIG. a, wherein FIG. b is a scanning electron microscope image of the quaternary ammonium-modified PPACE-Cl nanofibers; Figure 4 The water contact angle diagram of PPACE nanofibers and quaternary ammonium modified PPACE-Cl nanofibers in specific embodiment 3 of the present invention; Figure 5 The effect of pH on the adsorption process in the specific embodiment of the present invention is analyzed, wherein Figure a shows the effect of pH on the adsorption of AuCl4 - Figure a is the analysis diagram of the influence of pH on the adsorption amount; Figure b is the analysis diagram of the influence of pH on the Zata potential; Figure 6 In the specific embodiment of the present invention, different AuCl4 - Analysis of the effect of initial concentration on the adsorption process; Figure 7 This is an analysis diagram of the influence of different time on the adsorption process in a specific embodiment of the present invention; Figure 8 The quaternized PPACE-Cl nanofibers in the mixed solution react with AuCl4 in the specific embodiment of the present invention. - Selective impact analysis diagram; Fig. 9 This is an analysis diagram of the effect of temperature on the adsorption process in a specific embodiment of the present invention. DETAILED DESCRIPTION
[0020] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0021] Example 1
[0022] like Figure 1 and Figure 2 As shown, the present invention provides a method for preparing quaternary ammonium modified PPACE-Cl nanofibers, which specifically comprises the following steps: S1. Preparation of PAN electrospinning nanofibers: 0.6 g of polyacrylonitrile, polyvinyl pyrrolidone and carboxylated multi-walled carbon nanotubes and 9.6 g of N, N-dimethylformamide (DMF) were added to a beaker, and a uniform and transparent spinning solution was obtained after stirring at room temperature for 6 h. The obtained spinning solution was then placed in a 10 mL syringe and spun in an electrospinning machine. The optimized parameters of the spinning machine were set as follows: voltage of 15.0 KV, spinning solution flow rate of 2.0 mL / h, drum speed of 200 r / min, receiving distance of 15 cm, spinning temperature and humidity of 25 ± 1 °C and 70 ± 5%, respectively, to obtain PAN / PVP / MWCNT-COOH nanofibers. The obtained PAN / PVP / MWCNT-COOH nanofibers were then placed in 60 °C hot water to remove PVP, to obtain PAN / MWCNT-COOH nanofibers. S2. Preparation of nitrogen-enriched modified PPACE nanofibers: 0.2 g of the PAN / MWCNT-COOH nanofibers prepared in step S1 were weighed and placed in a high-pressure reactor with 2.0 g of a 10% polyethyleneimine (PEI) aqueous solution, and reacted at 110°C for 12 h. After the reaction, the nanofibers were washed with pure water for more than 3 times, and vacuum-freeze-dried at -50°C for 12 h to obtain modified PPACE nanofibers. S3. Preparation of quaternized PPACE-Cl nanofibers: After mixing the PPACE nanofibers prepared in step S2 with n-propyl chloride, ethanol was added as a solvent, and the mixture was refluxed at 80°C with magnetic stirring for 8 h. After the reaction, the nanofibers were washed with ethanol three times, and vacuum freeze-dried at -50°C for 12 h to obtain quaternized PPACE-Cl nanofibers; The quaternary ammonium modified PPACE-Cl nanofibers prepared by the above method are used as adsorption materials for gold recovery in wastewater.
[0023] Polyacrylonitrile (PAN) is a common material for electrospinning. It has good thermal stability and solvent resistance and is an ideal substrate material for electrospun nanofibers (ENMs). PAN electrospun nanofibers have small pore size, low porosity, high mechanical properties and stable morphological structure, and are widely used in the preparation of electrospun fibers. Carbon nanotubes (MWCNT-COOH) have potential in the mass transfer of metal ions in water due to the hydrophilicity and conductivity of the carboxyl group, as well as high tensile strength and chemical stability. Polyethyleneimine (PEI) has high hydrophilicity and a large number of coordinating groups, and can form complexes with metal anions under acidic conditions.
[0024] Electrospinning technology can produce nanofibers with a high specific surface area. The fiber surface is functionalized with nitrogen through surface grafting modification technology to provide more nitrogen active sites. The surface is then modified with a large number of positive charges. In addition, since the carboxylated carbon nanotubes introduced by electrospinning and the polyethyleneimine introduced by grafting have a large number of hydrophilic groups and exhibit good hydrophilicity, the energy barrier of the adsorbent contacting gold in the solution can be reduced, which significantly improves the adsorption effect of gold in the solution.
[0025] The present invention uses polyacrylonitrile (PAN), polyvinyl pyrrolidone (PVP) and carboxylated multi-walled carbon nanotubes (MWCNT-COOH) as matrix materials, adopts electrospinning technology to prepare nanofibers, uses polyethyleneimine (PEI) as a nitrogen-enriched functional group, and then uses chlorinated n-propane for quaternary modification to prepare quaternary ammonium modified PPACE-Cl nanofibers. The prepared quaternary ammonium PPACE-Cl nanofibers are reacted with AuCl4 - The AuCl4 is ionized by the electrostatic interaction, coordination interaction and redox interaction between the solutions. - In addition, the quaternary ammonium modified PPACE-Cl nanofibers prepared by the present invention have excellent hydrophilicity, reduce the energy barrier in the adsorption process, and can significantly improve the adsorption rate and adsorption capacity.
[0026] Example 2
[0027] The present invention provides a method for preparing quaternary ammonium modified PPACE-Cl nanofibers, which specifically comprises the following steps: S1. Preparation of PAN electrospinning nanofibers: 1.0 g of polyacrylonitrile, polyvinyl pyrrolidone and carboxylated multi-walled carbon nanotubes and 9.0 g of N, N-dimethylformamide (DMF) were added to a beaker, and a uniform and transparent spinning solution was obtained after stirring at room temperature for 12 h. The obtained spinning solution was then placed in a 10 mL syringe and spun in an electrospinning machine. The optimized parameters of the spinning machine were set as follows: voltage of 18.0 KV, spinning solution flow rate of 3.0 mL / h, drum speed of 200 r / min, receiving distance of 15 cm, spinning temperature and humidity of 25 ± 1 °C and 70 ± 5%, respectively, to obtain PAN / PVP / MWCNT-COOH nanofibers, and then the obtained nanofibers were placed in 100 °C hot water to remove PVP to obtain PAN / MWCNT-COOH nanofibers. S2. Preparation of nitrogen-enriched modified PPACE nanofibers: 0.5 g of the PAN / MWCNT-COOH nanofibers prepared in step S1 was weighed and placed in a high-pressure reactor with 5.0 g of a 10% polyethyleneimine (PEI) aqueous solution, and reacted at 140°C for 24 h. After the reaction, the nanofibers were washed with pure water for more than 3 times, and vacuum-freeze-dried at -50°C for 12 h to obtain modified PPACE nanofibers. S3. Preparation of quaternized PPACE-Cl nanofibers: Weigh 0.48 g of the PPACE nanofibers prepared in step S2, then weigh 1.332 g of n-propyl chloride and place them in a three-necked flask, add 100 mL of ethanol as a solvent, and reflux the reaction at 80°C with magnetic stirring for 12 h. After the reaction, the nanofibers are washed three times with ethanol, and vacuum freeze-dried at -50°C for 12 h to obtain quaternized PPACE-Cl nanofibers.
[0028] The quaternary ammonium modified PPACE-Cl nanofibers prepared by the above method are used as adsorption materials for gold recovery in wastewater.
[0029] Example 3
[0030] The present invention provides a method for preparing quaternary ammonium modified PPACE-Cl nanofibers, which specifically comprises the following steps: S1. Preparation of PAN electrospinning nanofibers: 0.7 g of polyacrylonitrile, polyvinyl pyrrolidone and carboxylated multi-walled carbon nanotubes and 9.1 g of N, N-dimethylformamide (DMF) were added to a beaker, and a uniform and transparent spinning solution was obtained after stirring at room temperature for 10 h. The obtained spinning solution was then placed in a 10 mL syringe and spun in an electrospinning machine. The optimized parameters of the spinning machine were set as follows: voltage of 18.0 KV, spinning solution flow rate of 3.0 mL / h, drum speed of 200 r / min, receiving distance of 15 cm, spinning temperature and humidity of 25 ± 1 ℃ and 70 ± 5%, respectively, to obtain PAN / PVP / MWCNT-COOH nanofibers, and then the obtained nanofibers were placed in 70°C hot water to remove PVP to obtain PAN / MWCNT-COOH nanofibers. S2. Preparation of nitrogen-enriched modified PPACE nanofibers: 0.4 g of the PAN / MWCNT-COOH nanofibers prepared in step S1 was weighed and placed in a high-pressure reactor with 4.0 g of a 10% polyethyleneimine (PEI) aqueous solution, and reacted at 120°C for 15 h. After the reaction, the nanofibers were washed with pure water for more than 3 times, and vacuum-freeze-dried at -50°C for 12 h to obtain modified PPACE nanofibers. S3. Preparation of quaternized PPACE-Cl nanofibers: Weigh 0.48 g of the PPACE nanofibers prepared in step S2, then weigh 1.128 g of n-propyl chloride and place them in a three-necked flask, add 100 mL of ethanol as a solvent, and reflux the reaction at 80°C with magnetic stirring for 9 h. After the reaction, the nanofibers are washed three times with ethanol, and vacuum freeze-dried at -50°C for 12 h to obtain quaternized PPACE-Cl nanofibers.
[0031] The quaternary ammonium modified PPACE-Cl nanofibers prepared by the above method are used as adsorption materials for gold recovery in wastewater.
[0032] Example 4
[0033] The present invention provides a method for preparing quaternary ammonium modified PPACE-Cl nanofibers, which specifically comprises the following steps: S1. Preparation of PAN electrospinning nanofibers: 0.9 g of polyacrylonitrile, polyvinyl pyrrolidone and carboxylated multi-walled carbon nanotubes and 13.5 g of N, N-dimethylformamide (DMF) were added to a beaker, and a uniform and transparent spinning solution was obtained after stirring at room temperature for 7 h. The obtained spinning solution was then placed in a 10 mL syringe and spun in an electrospinning machine. The optimized parameters of the spinning machine were set as follows: voltage of 18.0 KV, spinning solution flow rate of 3.0 mL / h, drum speed of 200 r / min, receiving distance of 15 cm, spinning temperature and humidity of 25 ± 1 °C and 70 ± 5%, respectively, to obtain PAN / PVP / MWCNT-COOH nanofibers, and then the obtained nanofibers were placed in 90 °C hot water to remove PVP to obtain PAN / MWCNT-COOH nanofibers. S2. Preparation of nitrogen-enriched modified PPACE nanofibers: 0.3 g of the PAN / MWCNT-COOH nanofibers prepared in step S1 were weighed and placed in a high-pressure reactor with 3.0 g of a 10% polyethyleneimine (PEI) aqueous solution, and reacted at 130°C for 15 h. After the reaction, the nanofibers were washed with pure water for more than 3 times, and vacuum-freeze-dried at -50°C for 12 h to obtain modified PPACE nanofibers. S3. Preparation of quaternized PPACE-Cl nanofibers: Weigh 0.48 g of the PPACE nanofibers prepared in step S2, then weigh 0.648 g of n-propyl chloride and place them in a three-necked flask, add 100 mL of ethanol as a solvent, and reflux the reaction at 80°C with magnetic stirring for 11 h. After the reaction, the nanofibers are washed with ethanol for at least 3 times, and vacuum freeze-dried at -50°C for 12 h to obtain quaternized modified PPACE-Cl nanofibers.
[0034] The quaternary ammonium modified PPACE-Cl nanofibers prepared by the above method are used as adsorption materials for gold recovery in wastewater.
[0035] Example 5
[0036] The present invention provides a method for preparing quaternary ammonium modified PPACE-Cl nanofibers, which specifically comprises the following steps: S1. Preparation of PAN electrospinning nanofibers: 0.8 g of polyacrylonitrile (PAN), polyvinyl pyrrolidone (PVP), carboxylated multi-walled carbon nanotubes (MWCNT-COOH, CNT for short) and 9.2 g of N, N-dimethylformamide (DMF) were added to a beaker, and a uniform and transparent spinning solution was obtained after stirring at room temperature for 8 h. The obtained spinning solution was then placed in a 10 mL syringe and spun in an electrospinning machine. The optimized parameters of the spinning machine were set as follows: voltage of 18.0 KV, spinning solution flow rate of 2.0 mL / h, roller speed of 200 r / min, receiving distance of 15 cm, spinning temperature and humidity of 25 ± 1°C and 70 ± 5%, respectively, to obtain PAN / PVP / MWCNT-COOH nanofibers (PAN / PVP / CNT for short), and the obtained nanofibers were then placed in 80°C hot water to remove PVP, to obtain PAN / MWCNT-COOH nanofibers (PPAC for short). S2. Preparation of nitrogen-enriched modified PPACE nanofibers: 0.5 g of the PAN / MWCNT-COOH nanofibers prepared in step S1 was weighed and placed in a high-pressure reactor with 5.0 g of a 10 wt% polyethyleneimine (PEI) aqueous solution, and reacted at 130°C for 20 h. After the reaction, the nanofibers were washed with pure water for more than 3 times, and vacuum-freeze-dried at -50°C for 12 h to obtain modified PPACE nanofibers. S3. Preparation of quaternized PPACE-Cl nanofibers: Weigh 0.48 g of the PPACE nanofibers prepared in step S2, then weigh 0.888 g of n-propyl chloride and place them in a three-necked flask, add 100 mL of ethanol as a solvent, and reflux the reaction at 80°C with magnetic stirring for 10 h. After the reaction, the nanofibers are washed three times with ethanol, and vacuum freeze-dried at -50°C for 12 h to obtain quaternized PPACE-Cl nanofibers.
[0037] The quaternary ammonium modified PPACE-Cl nanofibers prepared by the above method are used as adsorption materials for gold recovery in wastewater.
[0038] Sample characterization of this example: like Figure 3As shown in the figure, the surface morphology of the original PAN / MWCNT-COOH nanofibers (wt=8%) and the quaternary ammonium modified PPACE-Cl nanofibers (wt=8%) were observed by scanning electron microscopy. It can be clearly observed that the original PAN / MWCNT-COOH nanofibers (wt=8%) have a uniform diameter and no beading phenomenon, showing a network structure with a diameter mainly distributed around 600 nm. Due to grafting and modification, the quaternary ammonium modified PPACE-Cl fibers become thicker than the original PAN / MWCNT-COOH fibers after modification. On the other hand, Figure 4 As shown in the figure, the quaternary ammonium modified PPACE-Cl fibers have super hydrophilicity due to the introduction of a large number of hydrophilic groups. In short, the changes in the morphology of the modified fibers show that the quaternary ammonium modification on the surface of the nanofibers is successful and has super hydrophilicity.
[0039] Considering the influence of different factors on the adsorption results, static adsorption was used to investigate the adsorption of AuCl4 by PPACE-Cl nanofibers under different conditions. - The adsorption capacity of Au(Ⅲ) was studied. The influencing factors mainly include solution pH (1-6), initial concentration of Au(Ⅲ) solution (100-550 mg / L), adsorption temperature (25-45℃) and contact time (1-3000 min). The whole adsorption process was carried out in a constant temperature oscillator. - The concentration was determined by ICP-OES. The theoretical adsorption capacity was calculated according to the following formula: The adsorption amount (mg / g) of the adsorbent was calculated according to the following formula (1): ; Where: Q e (mg / g) is the adsorption capacity; C0 (mg / L) is the initial concentration of the solution; C e (mg / L) is the equilibrium concentration of the solution; V (mL) is the volume of the solution; W (g) is the mass of the adsorbent.
[0040] like Figure 5 As shown in Figure 2, PPACE-Cl nanofibers showed good kinetics for AuCl4 in a wide pH range (2-3). - It has a good adsorption effect, and has the best adsorption capacity at pH=2. When the pH is greater than 3, the adsorption capacity begins to gradually decrease. The reason for this phenomenon can be explained by the Zeta potential in the figure. It is mainly because when the pH is less than 7.68, the surface of the adsorbent material PPACE-Cl nanofiber has a positive charge, which is easy to react with the negatively charged AuCl4 - The adsorption behavior occurs between them through electrostatic attraction.
[0041] In order to study the effect of initial concentration on the adsorption capacity of PPACE-Cl nanofibers, AuCl4 with a concentration of 100-550 mg / L was prepared. - The experiment was carried out at 25°C and the pH value of the solution was 2. Figure 6 It can be seen that as the concentration increases, the adsorption capacity is positively correlated with the initial concentration. - When the initial concentration reaches 400 mg / L, the adsorption basically reaches saturation.
[0042] The effect of contact time on the adsorption process is as follows Figure 7 As shown in the figure, the adsorption capacity increased rapidly within the initial contact time of 2200 min. This may be because the PPACE-Cl nanofibers have a large number of adsorption sites at this time. After that, the adsorption rate climbed relatively slowly, and the adsorption basically reached equilibrium at 3000 min. This result may be related to the fact that the adsorption sites of the PPACE-Cl nanofibers were largely occupied. In addition, a large amount of Au 3+ Adsorption leads to a decrease in the ion concentration in the solution, thereby weakening the driving force for mass transfer.
[0043] The selectivity experiment was conducted by adding 10 mg of PPACE-Cl nanofibers into 25 mL of a mixed solution containing 200 mg / L of Fe(III), Co(II), Ni(II), Cd(II), Pb(II) and Au(III). The results are shown in Table 1. Figure 8 As shown, PPACE-Cl nanofibers have a 3+ It showed high adsorption capacity, but had little adsorption to other ions. - The excellent selectivity of PPACE-Cl nanofibers for AuCl4 - The selectivity of the ion is attributed to its surface rich in positive charges, which easily react with AuCl4 in the form of negative ions. - Static electricity is generated between them.
[0044] In addition, it should be noted that, based on the same principle, the selective adsorption effect of the quaternary ammonium modified PPACE-Cl nanofibers provided by the present invention is not limited to AuCl4 in a mixed solution of Fe(III), Co(II), Ni(II), Cd(II), Pb(II) and Au(III). - Specific recognition.
[0045] The effect of temperature on the adsorption process was investigated by thermodynamic experiments at different temperatures of 25°C-45°C (contact time 2200 min, pH = 2). The results are as follows: Fig. 9As shown. It can be concluded that within a certain temperature range, as the temperature gradually rises, the adsorption material for AuCl4 - The adsorption capacity of AuCl4 - This result may be due to the fact that AuCl4 - The rate of diffusion is accelerated.
[0046] 10 mg of different nanofibers obtained in each step of this example were placed in 25 mL of a solution containing 263.8 mg / L Au(III) for adsorption. The adsorption capacity of each nanofiber is shown in Table 1 below: Table 1 Comparison of adsorption capacity of nanofibers obtained at different stages of modification ; As can be seen from Table 1, the adsorption capacity of PPACE-Cl nanofibers modified by quaternization is greatly improved.
[0047] Comparative Example 1
[0048] The present invention provides a method for preparing quaternary ammonium modified PPACE-Cl nanofibers, which specifically comprises the following steps: S1. Preparation of PAN electrospinning nanofibers: Add 0.8 g of polyacrylonitrile (PAN), polyvinyl pyrrolidone (PVP) and 9.2 g of N, N-dimethylformamide (DMF) to a beaker, stir at room temperature for 8 h to obtain a uniform and transparent spinning solution, then place the obtained spinning solution in a 10 mL syringe and spin it in an electrospinning machine; the optimized spinning machine parameters are set as follows: voltage is 18.0 KV, spinning solution flow rate is 2.0 mL / h, roller speed is 200 r / min, receiving distance is 15 cm, spinning temperature and humidity are 25 ± 1 ℃ and 70 ± 5%, respectively, to obtain PAN / PVP nanofibers. The nanofibers are placed in 80°C hot water to remove PVP to obtain porous polyacrylonitrile nanofibers; S2. Preparation of modified nanofibers: 0.5 g of the polyacrylonitrile nanofibers prepared in step S1 was weighed, and the mixture was placed in a high-pressure reactor with 5.0 g of a 10 wt% polyethyleneimine (PEI) aqueous solution, and reacted at 130° C. for 20 h. After the reaction, the nanofibers were washed with pure water for more than 3 times, and vacuum-freeze-dried at -50° C. for 12 h to obtain modified nanofibers. The modified nanofibers prepared by the above method are placed in wastewater as adsorption materials.
[0049] Adsorption test: 10 mg of each of the quaternized modified PPACE-Cl nanofibers prepared in Examples 1-5 and the modified nanofibers prepared in Comparative Example 1 were taken, and a certain volume of wastewater solution was taken out from the wastewater pool at the same time. The pH value of the wastewater solution was adjusted to pH = 2 using hydrochloric acid, and then 6 portions of wastewater solution with the same volume of 25 mL were measured from the acid-adjusted wastewater solution, and the weighed quaternized modified PPACE-Cl nanofibers and modified nanofibers were placed in the 6 portions of wastewater solution, respectively. The temperature was controlled at 25 ° C and the modified nanofibers were taken out after constant temperature oscillation for 8 h. The concentrations of each metal ion in the solution before and after adsorption were determined by inductively coupled plasma emission spectrometry (ICP-OES). The initial concentrations of each ion in the wastewater solution before adsorption were: Au (III) 263.8 mg / L, Co (II) 208.6 mg / L, Fe (III) 201.5 mg / L, Ni (II) 205.3 mg / L, Pb (II) 210.9 mg / L, after the concentration of each metal ion in the wastewater solution is determined after adsorption, the adsorption capacity of each nanofiber for each metal in the wastewater is calculated. The above experiment is repeated three times and the average value is taken, that is, the nanofiber of each embodiment and comparative example is subjected to three repeated adsorption tests, and the adsorption capacity data are shown in Table 2: Table 2 Adsorption capacity of metal ions of each nanofiber obtained by the method of Examples 1-5 and Comparative Example 1 ; It can be seen from the data in Table 2 that the quaternary ammonium modified PPACE-Cl nanofibers AuCl4 prepared by the preparation method of the quaternary ammonium modified PPACE-Cl nanofibers provided in this application - It has excellent specific adsorption capacity for AuCl4 - The quaternary ammonium modified PPACE-Cl nanofibers have excellent hydrophilicity, reduce the energy barrier in the adsorption process, and can significantly increase the adsorption rate and adsorption capacity. They can be used to recover gold from wastewater. - It exhibits excellent specific adsorption capacity and has very small adsorption capacity for other heavy metals, which greatly simplifies the subsequent purification process of recovered gold, improves the efficiency of the gold recovery process, and has high industrial value.
[0050] The preferred embodiments of the present invention are described above with reference to the accompanying drawings. A person skilled in the art may implement the present invention in a variety of variations without departing from the scope and essence of the present invention. For example, a feature shown or described as part of one embodiment may be used in another embodiment to obtain another embodiment. The above are only preferred feasible embodiments of the present invention, and do not limit the scope of rights of the present invention. Any equivalent changes made using the contents of the present specification and the accompanying drawings are included in the scope of rights of the present invention.
Claims
1. A method for preparing quaternary ammonium modified PPACE-Cl nanofibers, characterized in that: The specific steps include: S1. Preparation of PAN electrospinning nanofibers: polyacrylonitrile, polyvinyl pyrrolidone, and carboxylated multi-walled carbon nanotubes were stirred with N,N-dimethylformamide at room temperature for 6-12 hours to obtain a uniform and transparent spinning solution, and then the obtained spinning solution was placed in a 10 mL syringe and spun in an electrospinning machine to obtain PAN / PVP / MWCNT-COOH nanofibers, and then the obtained nanofibers were placed in 60-100°C hot water to remove PVP to obtain PAN / MWCNT-COOH nanofibers; S2. Preparation of nitrogen-enriched modified PPACE nanofibers: placing the PAN / MWCNT-COOH nanofibers prepared in step S1 and an aqueous solution of polyethyleneimine in a high-pressure reactor, reacting at 110-140°C for 12-24h, washing the nanofibers after the reaction with pure water for more than 3 times, and performing vacuum freeze drying at -50°C for 12h to obtain modified PPACE nanofibers; S3. Preparation of quaternized PPACE-Cl nanofibers: After mixing the PPACE nanofibers prepared in step S2 with n-propyl chloride, ethanol was added as a solvent, and refluxed for 8 to 12 hours under magnetic stirring at 80°C. After the reaction, the nanofibers were washed with ethanol three times, and vacuum freeze-dried at -50°C for 12 hours to obtain quaternized modified PPACE-Cl nanofibers.
2. The method for preparing a quaternary ammonium modified PPACE-Cl nanofiber according to claim 1, characterized in that: The mass ratio of the polyacrylonitrile, polyvinyl pyrrolidone, carboxylated multi-walled carbon nanotubes and N,N-dimethylformamide is 1:1:1:9-16.
3. The method for preparing a quaternary ammonium modified PPACE-Cl nanofiber according to claim 1, characterized in that: The mass ratio of the PAN / MWCNT-COOH nanofibers to the polyethyleneimine aqueous solution is 1:
10.
4. The method for preparing a quaternary ammonium modified PPACE-Cl nanofiber according to claim 1, characterized in that: The mass ratio of the PPACE nanofiber to the n-propyl chloride is 1:0.925-2.
775.
5. The method for preparing a quaternary ammonium modified PPACE-Cl nanofiber according to claim 1, characterized in that: The parameters of the electrospinning machine were set as follows: voltage of 15.0-18.0 KV, spinning solution flow rate of 2.0 mL / h, drum speed of 200 r / min, receiving distance of 15 cm, spinning temperature and humidity of 25 ± 1 °C and 70 ± 5%, respectively.
6. A quaternary ammonium modified PPACE-Cl nanofiber, characterized in that: The quaternary ammonium modified PPACE-Cl nanofiber is prepared by the preparation method of the quaternary ammonium modified PPACE-Cl nanofiber described in any one of claims 1 to 5.
7. An application of quaternary ammonium modified PPACE-Cl nanofibers, characterized in that: The quaternary ammonium modified PPACE-Cl nanofiber of claim 6 is used as an adsorption material for AuCl4 - Selective recovery.
Citation Information
Patent Citations
Functionalized polyethylenimine-grafted porous nano-fiber adsorption material and preparation thereof
CN106975465A
Carbon nanofiber, diffusion layer, membrane electrode, fuel cell and preparation method and application thereof
CN111584886A
Preparation of PEI-PAN-Ppy core-shell structure nanofiber membrane and application of PEI-PAN-Ppy core-shell structure nanofiber membrane in chromium ion adsorption
CN112657476A
Amino-rich polyacrylonitrile-based nano-composite fiber membrane as well as preparation method and application thereof
CN115262232A
Preparation method and application of branched polyethyleneimine grafted porous polyacrylonitrile nanofiber membrane adsorbent
CN117966481A